Pollution and moisture infiltration effect assessment based on data-driven analysis for aircraft heritage protection - Oswald, Cyril; Kuchař, Michal; Fišer, Jaromír; Khol, Miroslav; Oswaldová, Ivana; Simeunović, Goran; Vyhlídal, Tomáš; Robbiola, Luc; Brunet, Magali; Monticelli, Cecilia; Balbo, Andrea; Chiavari, Cristina; et al. (E3S web of conferences, 2022)
The paper deals with monitoring and analyzing the indoor environmental parameters through remote data collection to evaluate the pollution and moisture infiltration effects on aircraft heritage conservation. First, based on the meteorological and pollution data, the moisture penetration and airborne pollution infiltration into indoor spaces of a heritage site (hangar) with stored historic aircrafts are determined. The hangar under investigation is located in the Aviation museum Kbely, Prague, Czech Republic. The determination is performed by wet/dry cycles (fluctuations) evaluation and applying ISO 11844 methodology to outdoor pollution infiltration into the interior. Next, a time of wetness (ToW) is determined indoors according to ISO 9223, rather as an environmental than a surface parameter as dewing and exceeding high humidity level (approxl RH 80% at T >0 °C) are considered. The actual moisture adsorption onto polluted surfaces of aircraft artifacts is then dependent on the hygroscopic corrosion products developed. Such an adsorption prolongs actual surface ToW. In addition to ToW, even the deposition rate of indoor pollutants, particularly sulphur dioxide and chlorides, are considered and the atmosphere corrosivity is estimated by applying the ISO standardized statistical models for aluminium. The resulting iso-corrosivity figures out the aggressiveness of the hangar environment from the point of view of aircraft material susceptibility to corrosion and degradation.